HOW GOVERNMENT REGULATION NO. 6 OF 2021 ARTICLES 7 AND 38 INFLUENCES THE IMPLEMENTATION OF BUSINESS LICENSING IN INDONESIAN REGIONS - Nana Sugiarti; Harun Harun; Nunik Nurhayati; Arief Budiono (RADJA PUBLIKA, 2026)
This study examines the legal implications of Articles 7 and 38 of Government Regulation No. 6 of 2021 on the Implementation of Business Licensing in the Regions and their influence on regional business licensing administration in Indonesia. The research aims to analyze how these provisions reshape the institutional framework for implementing risk-based business licensing through the establishment of Independent One-Stop Integrated Service Agencies at the provincial and regency/city levels. The authors utilized a socio-legal approach combining doctrinal and empirical legal research methods through statutory analysis, literature review, field observations, and interviews with relevant government officials, using Karanganyar Regency as a case study. The findings demonstrate that the Regulation requires regional governments to reorganize their licensing institutions by separating Independent One-Stop Integrated Service Agencies from other governmental affairs, standardizing organizational structures, and integrating licensing services with the Online Single Submission (OSS) system. These reforms are intended to enhance legal certainty, administrative efficiency, transparency, and investment facilitation while ensuring consistency with the hierarchy of Indonesian legislation. The study concludes that Government Regulation No. 6 of 2021 has significantly strengthened regional business licensing governance by providing a clear legal framework for institutional restructuring and improving the effectiveness of investment services across regional governments.